A modular UAV hardware platform for aerial indoor navigation research and development - Deliparaschos, Kyriakos M.; Loizou, Savvas G.; Zolotas, Argyrios C. (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This study introduces a specialised hardware plat-form designed for indoor navigation, featuring a quadrotor equipped with either a NVIDIA Jetson Nano or a Z-turn Zynq onboard computer. The onboard computer communicates via ROS2 with the flight controller, the Inertial Measurement Unit (IMU), Ultra-WideBand (UWB) localisation system, stereo camera, Light Detection and Ranging (LiDAR), and ultrasonic sensors. The focus is on creating a low-cost modular Unmanned Aerial Vehicle (UAV) system adaptable to various indoor navigation applications. The modular design encompasses different onboard computer platforms and sensor configurations, allowing for easy adaptation to research experiment setups. The objective is to facilitate the transition from simulated and simplified laboratory experiments to deploying aerial robots in challenging real-world conditions. The paper explores the hardware architecture and Robot Operating System 2 (ROS2)-based communication system of the UAV and provides a weight analysis and power estimation.